2016
DOI: 10.1108/ijccsm-03-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

The use of indigenous knowledge systems for short and long range rainfall prediction and farmers’ perceptions of science-based seasonal forecasts in Zimbabwe

Abstract: Purpose This paper aims to document indigenous knowledge systems (IKS) used for short- and long-range rainfall prediction by small holder farmers in three communities of Guruve District, in north-eastern Zimbabwe. The study also investigated farmers’ perceptions of contemporary forecasts and the reliability of both IKS and contemporary forecasts. Design/methodology/approach Data were collected among small holder farmers in Guruve District using household interviews and focus group discussions in three wards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Farmers' perceptions of climate change in the study area are in line with empirical data and other studies on farmers perceptions inhabiting marginal areas in Zimbabwe [ 23 , 41 , 42 ]. Findings are also similar to other studies in Zimbabwe such as Guruve District where Gwenzi et al [ 43 ] and Hwedza and Makoni [ 44 ] have reported unpredictable rainfall, declining rainfall, and increasing temperatures as some of the indicators of climate change. Local ecological knowledge on climate patterns and impacts has been documented in other studies in different parts of Africa [ 45 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…Farmers' perceptions of climate change in the study area are in line with empirical data and other studies on farmers perceptions inhabiting marginal areas in Zimbabwe [ 23 , 41 , 42 ]. Findings are also similar to other studies in Zimbabwe such as Guruve District where Gwenzi et al [ 43 ] and Hwedza and Makoni [ 44 ] have reported unpredictable rainfall, declining rainfall, and increasing temperatures as some of the indicators of climate change. Local ecological knowledge on climate patterns and impacts has been documented in other studies in different parts of Africa [ 45 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…This limits the acceptability and use of forecast information (Cash et al,2003;Okello et al, 2012;Karpouzoglou et al, 2016). Consequently, local farmers across Africa highly depend on indigenous forecasts for most farm decision making, including in Ghana (Gyampoh et al, 2009;Nyantakyi-Frimpong, 2013), Zimbabwe (Gwenzi et al, 2016), Burkina Faso (Roncoli et al, 2002) and South Africa (Zuma-Netshiukhwi et al, 2013).…”
Section: Background and Problem Outlinementioning
confidence: 99%
“…The survey revealed that adaptive farm decisions of farmers are generally based on information generated from indigenous and scientific forecasts. While farmers were quick to acknowledge the limitations in their personal forecast they, however, considered it better for decision making than the scientific forecast provided by Ghana Meteorological Agency as this was perceived to be generic and not locally specific to their community and needs (See also Gwenzi et al, 2016;Zuma-Netshiukhwi et al, 2013). Information systems within the study area were identified to provide scientific forecast information whereas indigenous forecasts were tied to farmers' observation matched with experience.…”
Section: Socio-institutional Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey revealed that adaptive farm decisions of farmers are generally based on information generated from indigenous and scientific forecasts. While farmers were quick to acknowledge the limitations in their personal forecast they however considered it better for decision making than the scientific forecast provided by Ghana Meteorological Agency as this was perceived to be generic and not locally specific to their community and needs (see also Gwenzi, Mashonjowa, Mafongoya, Rwasoka, & Stigter, 2016;Zuma-Netshiukhwi, Stigter, & Walker, 2013). Information systems within the study area were identified to provide scientific forecast information whereas indigenous forecasts were tied to farmers observation matched with experience.…”
Section: I)mentioning
confidence: 99%